Elevated first-trimester neutrophil elastase and proteinase 3 increase the risk of gestational diabetes mellitus and adverse fetal outcomes - Lihong Wang; Zhoujunhao Zhou; Xinming Xu; Yue Li; Rui Zhang; Zhiyan Yu; Xinmei Huang; Shufei Zang; Tiange Sun (BMC, 2024)
Abstract Background Chronic inflammation plays a vital role in the development of gestational diabetes mellitus (GDM). Studies in mouse models show that neutrophil serine proteases (NSPs), neutrophil elastase (NE) and proteinase-3 (PR3) are important drivers of chronic inflammation with consequent metabolic disturbances. This study evaluated the association of NE and PR3 with GDM development and adverse fetal outcomes. Method(s) This was a prospective cohort study. Serum PR3 and NE concentration was measured in all enrolled pregnant women in the first and the second trimester to determine the connection between NSPs and GDM and adverse fetal outcomes. Logistic regression, spline regression and linear regression analyses were applied to investigate the association of NE or PR3 with GDM development and adverse fetal outcomes. The concentration of NE and PR3 in placental biopsies was evaluated by semi-quantitative analysis of immunohistochemistry staining. Result(s) NE or PR3 concentration in the first trimester, rather than the second, increased more significantly in women with GDM than in those without, regardless of pre-pregnancy body mass index and age. There was a stepwise increase in GDM occurrence as well as comprehensive adverse fetal outcomes across tertiles of NE and PR3. NE and PR3 were positively associated with neutrophil count, pre-pregnancy BMI, plasma glucose level and newborn weight. Logistic regression revealed NE or PR3 to be independent risk factors for the development of GDM and comprehensive adverse fetal outcomes. Spline regression showed a significant increased risk of GDM occurrence and comprehensive adverse fetal outcomes when serum NE concentration exceeded 417.60 ng/mL and a similar result for PR3 and GDM occurrence when the latter exceeded 88.52 ng/mL. Immunohistochemistry data confirmed that enriched NE and PR3 content in placental tissue may have contributed to the development of GDM. Conclusion(s) This work demonstrates that excessive first-trimester NE and PR3 increase the risk of GDM development and comprehensive adverse fetal outcomes.